FORAMINIFERA SEBAGAI PENCIRI PALEO ENVIRONMENT: STUDI KASUS PADA LINTASAN KALI BENTUR, NGAWENAN, BLORA - -, Lili Fauzielly (Fakultas Teknik Geologi Universitas Padjadjaran, 2008)
Foraminifera analysis taken from 18 surface sample from sandstone unit and siltstone unit, Kali Bentur section, Ngawenan area, Blora.According quantitative analysis, foraminifera assemblages consist of 39 species (218.128 individu) planktonic and 53 species (16.384 individu) bentic , with abundance of Globigerinoides trilobus imaturus, Globigerinoides trilobus trilobus, Globoquadrina altispira, Globoquadrina dehiscens, Orbulina universa, Globorotalia menardii and Bolivina, Batisiphon, Cibicides, Robulus, Planulina, Uvigerina dan StilostomelaForaminifera planktonic distribution indicated tropical zone, warm water(24oC - 28oC ) salinity 34-36 ppm, and based on bentic foraminifera, there were paleoenvironment change that more deep from sandstone unit to silt unit.